A Charging and Discharging Model for Electric Vehicles based on Consortium Blockchain Using Multi-Objective Gray Wolf Algorithm - Shang, Xingyu; Li, Yuancheng; Huang, Rong (Recent Advances in Electrical & Electronic Engineering, 2022)
Background: Since many EVs (EVs) are connected to the grid, several issues occur with transactions between EVs and the grid, such as poor privacy and system instability. This paper uses consortium blockchain to design a safe and privacy-preserving scheme for the two-way power transaction between EVs and the grid. Objective: To reduce the adverse impact of disorderly charging of large-scale EVs on the power grid, the total load variance is minimized by optimizing EVs' charging/discharging period. Methods: We proposed to use a heuristic algorithm, an improved multi-objective gray wolf algorithm, to solve this problem. Results: The simulation results show that the model can effectively smooth load fluctuations and improve user benefits. Conclusion: Our method can effectively reduce the load fluctuation of the grid while ensuring the economic benefits of users. Qualitative security and privacy analysis show that the solution helps improve the security and privacy of electricity transactions.
Keywords: Electric vehicles